Identification of Recombinant Chimpanzee Adenovirus C68 Degradation Products Detected by AEX-HPLC - Powers, Thomas W.; Mullins, Elise K.; Zhang, Kun; Binder, Joseph J.; Friese, Olga; Runnels, Herbert A.; Thompson, Lawrence C. (Frontiers in Bioengineering and Biotechnology, 2022)
Physicochemical tests represent important tools for the analytical control strategy of biotherapeutics. For adenoviral modalities, anion-exchange high performance liquid chromatography (AEX-HPLC) represents an important methodology, as it is able to simultaneously provide information on viral particle concentration, product purity and surface charge in a high-throughput manner. During product development of an adenoviral-based therapeutic, an accelerated stability study was performed and showed changes in each of the AEX-HPLC reportable attributes. These changes also correlated with a decrease in product infectivity prompting a detailed characterization of the impurity and mechanism of the surface charge change. Characterization experiments identified the impurity to be free hexon trimer, suggesting that capsid degradation could be contributing to both the impurity and reduced particle concentration. Additional mass spectrometry characterization identified deamidation of specific hexon residues to be associated with the external surface charge modification observed upon thermal stress conditions. To demonstrate a causal relationship between deamidation and surface charge changes observed by AEX-HPLC, site-directed mutagenesis experiments were performed. Through this effort, it was concluded that deamidation of asparagine 414 was responsible for the surface charge alteration observed in the AEX-HPLC profile but was not associated with the reduction in infectivity. Overall, this manuscript details critical characterization efforts conducted to enable understanding of a pivotal physicochemical test for adenoviral based therapeutics.